The Feasibility and Applicability of Stem Cell Therapy for the Cure of Type 1 Diabetes - Ryota Inoue; Kuniyuki Nishiyama; Jinghe Li; Daisuke Miyashita; Masato Ono; Yasuo Terauchi; Jun Shirakawa (Cells, 2021)
Stem cell therapy using islet-like insulin-producing cells derived from human pluripotent stem cells has the potential to allow patients with type 1 diabetes to withdraw from insulin therapy. However, several issues exist regarding the use of stem cell therapy to treat type 1 diabetes. In this review, we will focus on the following topics: (1) autoimmune responses during the autologous transplantation of stem cell-derived islet cells, (2) a comparison of stem cell therapy with insulin injection therapy, (3) the impact of the islet microenvironment on stem cell-derived islet cells, and (4) the cost-effectiveness of stem cell-derived islet cell transplantation. Based on these various viewpoints, we will discuss what is required to perform stem cell therapy for patients with type 1 diabetes.